Evolutionary conservation of salinity responsive miRNAs from Indian wheat (Triticum aestivum) landrace, Kharchia Local - C, MAHENDRA; HRISHIKESHAN, KUMAR NUPUR; ISMAIL, AHMED MOHAMMED; JAIN, PRADEEP KUMAR; GAIKWAD, KISHOR; KUMAR, KANIKA (The Indian Journal of Agricultural Sciences, 2024)
Being temporal, majority of abiotic stresses induces responses in plants that needs to be regulated in energy efficient manner. These regulations are carried out by many regulatory molecules including microRNAs and transcription factors. Like protein coding genes, miRNAs are also conserved across the plant species to exhibit their conserved function during growth, development and response to biotic or abiotic stresses. The present study was carried out during 2020 and 2021 at National phytotron facility, ICAR-Indian Agricultural Research Institute, New Delhi. Control and salinity treated plants of Kharchia Local, a highly salt tolerant landrace of wheat (Triticum aestivum L.) from India, were grown in hydroponics and after sequencing and analysis of small RNA data, salinity responsive mature miRNA sequences from Kharchia Local were analyzed for their evolutionary relationship with sequences from the public databases. The phylogenetic study, sequence similarity (identity scores) and multiple sequence comparison was used for evolutionary conservation analysis. The study revealed that, miRNA sequences from Kharchia Local are diverse and did not group with the salinity responsive miRNAs from the database except miR1551. Interestingly, a total of 25 known or conserved miRNA families were identified as salinity responsive across the plant species. The miRNAs from Kharchia Local appears to play regulatory role in novel mechanisms of salinity tolerance.